PENGARUH LINGKUNGAN KELUARGA TERHADAP MINAT BELAJAR SISWA PADA MATA PELAJARAN PENDIDIKAN AGAMA ISLAM SMP MUHAMMADIYAH 5 KERJO KABUPATEN KARANGANYAR - Saputro, Imron Wahyu; Nurhidayati, Indah; AlFarisi, Salman (Jurnal Kepemimpinan dan Pengurusan Sekolah, 2025)
This study is motivated by the importance of the family environment, particularly parental attention, in shaping students’ interest in learning Islamic Religious Education (PAI). The objectives of this study are: (1) to identify the level of parental attention toward the learning interest of grade VII students of SMP Muhammadiyah 5 Kerjo in the 2024/2025 academic year, (2) to determine the level of students’ interest in learning PAI, and (3) to analyze the influence of the family environment on students’ learning interest in PAI. The study employed a quantitative associative approach. The population and sample consisted of 56 seventh-grade students selected using total sampling. Data were collected through questionnaires and documentation, and analyzed using validity, reliability, normality, linearity, and simple linear regression tests.NThe results show that parental attention is in the high category (60.07%), students’ learning interest is in the moderate category (51.8%), and 44.0% of the variation in students’ learning interest is influenced by the family environment, while the remaining 56.0% is influenced by other factors. These findings indicate that family attention significantly contributes to fostering students’ interest in PAI learning.